Utilization of xilo-oligosaccharides (as prebiotic) from enzimatic hydrolyzed corncob with endo-ß-xilanase - Tjahjandarie, Tjitjik Srie (Universiti Teknologi Malaysia, 2009)
Certain nondigestible oligosaccharides can be selectively utilized by probiotic and beneficial to gastrointestinal health. The objectives of this research are to identify that xylo-ologosaccharides (XOS) from corncob can be used as prebiotic and to purify XOS using Candida guilliermondii. XOS were yielded from hemicelluloses of corncob that enzymatically hydrolyzed with endo-ß-xilanase from Bacillus subtilis PC-01. TLC and HPLC analysis of hydrolised product shown that hemicelluloses B contains XOS higher than hemicelluloses A. XOS from corncob were purified using Candida guilliermondii. Candida guilliermondii metabolized monosaccharide, xylobiose and xylotriose, but leaves XOS with polymerization degree higher than xylotetrose. The purification products were analyzed by TLC and HPLC. Five percents of XOS from hemicelluloses B and hemicelluloses A was added to growth medium of Lactobacillus casei (probiotic). As the result, the number of probiotic was significantly increased. It means that XOS from corncob can be selectively fermented by Lactobacillus casei producing lactic acid and SCFA (Short-chain Fatty Acid). The fermentation products were analyzed by Gas Chromatography to asses SCFA concentration.